Media Massa dan Disintegrasi Bangsa - Moh. Yamin Rumra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article was written to examine and analyze the impact of the role of the mass media on the potential problems of the disintegration of the Indonesian nation which have been quite widespread lately. This article was written on the basis that the mass media can play a dual role as a factor of integration and disintegration, amidst the growth of press freedom as a result of the growth of democracy and democratization in Indonesia. This research is qualitative research with library research as the main data collection technique. This study found that the potential of the mass media can play a role in strengthening integration in society but at the same time can be a factor in the occurrence of disintegration. This really depends on the tendency of the media itself, whether the media tends to be centrifugal or tends to be centripetal. If the media tends to be centrifugal, it will speed up the process of disintegration, likewise if the mass media tends to be centripetal then it can become an adhesive and strengthen national integration.